The lost island : a Gideon Crew novel - Preston, Douglas J.; Child, Lincoln (New York : Grand Central Publishing, 2014)
After being tasked with stealing a page from a priceless, ancient book, brilliant scientist and master thief Gideon Crew discovers a hidden map on the back of the book's parchment, in the third novel of the series following Gideon's Corpse.
Keywords: Book of Kells -- Fiction; Islands -- Fiction; Book thefts -- Fiction; Dublin (Ireland) -- Fiction